Chemosensation in the marine annelid Platynereis dumerilii: anatomy, physiology, behaviour - Chartier, Thomas (2018)
Keywords: Chemosensation, marine, annelid, Platynereis dumerilii, calcium imaging, associative learning, microfluidics, neurobiology, evolution.